Nepal-China Relation: Tea Horse Road to Belt and Road Initiative - Basnyat, Laxmi (Historical Journal, 2023)
Nepal-China relationship is the oldest in the diplomatic history of Nepal. It is hard to find the beginning point. However, the evidence proves that Manjushree arrived from China to Kathmandu, then cut open a rocky hill called Chobhar to let the water from the enormous lake out whose mud when caked offered itself a fit place to live and cultivate. It is also important to note that the Tea and Horse Road back to the period of the Tang dynasty 618-907 and the Tibetan (Tubo) regime is the next evidence of Sino-Nepal relations, the oldest one. The Lichchhavi period, the Malla period, and the Gorkha Shah King dynasty are full of Sino-Nepal histories. The pilgrim trips from China and Tibet to Nepal and Nepalese trade with Tibet are the major sources of bilateral histories. The Military relationship is also very old, and it starts formally from the time of Kaji Bhim Malla’s military expedition in Tibet. Also, many wars took place between the two countries. However, we have got the best relation up to today and the military relation has been strengthening according to our diplomatic relations. I also would like to mention that the Sino-Nepal relationship has been running more formal rather than people-to-people communication due to our language and geographical barrier in comparison to our southern neighbor. There are many rooms to be researched from Ancient Tea and Horse Road onward present Belt and Road Initiative (BRI).